A glyco-competitive assay to demonstrate the stochasticity of fate decisions in Escherichia coli. (February 2017) - Simone, Giuseppina
Graphical abstract: Highlights: E. coli - glucose binding in solution and immobilized at the surface were studied. Glucose is the major source of carbon for the bacteria in deprived environment. Reaction equilibrium and adsorption constants were 8 mM −1 and 1 (cell/mL) −1 . Stochastic approach shows failure of biochemistry alone to describe E. coli behavior. E. coli privileged the anchored glucose after an initial transient. Abstract: Interaction bacteria-gut, via glycan associations, contribute to the selection of microbial communities along the gastrointestinal tract, influencing cancer development. The mechanism causing microbiome alterations is unknown, while this understanding would be pivotal to identify medical therapies. The molecular associations between Escherichia coli bacteria and glucose, both in solution and immobilized at the surface, were studied showing the dependence of E. coli glucose binding on the sugar form. Classical kinetic models were used to derive the reaction equilibrium and adsorption constants, 8 mM −1 and 1 (cell/mL) −1 and to explain the uptake. E. coli preferred the free glucose, whereas in a deprived environment, the anchored glucose became the major source of carbon for the bacteria. A stochastic algorithm disclosed that after initial transient, E. coli privileged the anchored glucose rather than the free sugar, independently on the concentration. The biochemical approach alone failed to describe the effective behavior of the cells and that several parameters can affect the behavior of the bacteria. From this result, more sophisticated models of the destruction of the gut barrier can be derived, such as the mechanism whereby E. coli can switch the immune system on and off to cause cancer and its metastasis.